Kontrahovanie služieb vo verejnom sektore - skúsenosti v Slovenskej a Českej republike - Mikušová Meričková, Beáta (Masaryk University Press, 2020)
Title in English: Contracting out services in public services - Slovak and Czech Republic experiencies The monograph responds to the issue of contracting out services in public sector. The aim of the monograph is to develop the theory of contracting out services in public sector and to propose solutions for the contract management in the public sector. To prove the assumption about low quality contract management in public sector in SR and CR as the reason of contracting out failure is the research issue developed from contracting out effectiveness to contract management quality. Original research issue - relationship between contracting out outcomes and quality contract management and innovative methodology testing this relationship brings valuable results in the dimension of contracting out theory in an international context and to define science-based ground for proposing solutions to the contract management in public sector.